ANALYSIS OF PARENTING LEARNING NEEDS - jaenal mutakim; Elais Retnowati (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2020)
The family is the first and foremost place of learning for children. Parents must be able to adjust and challenges to educate their childern to faced life in the future. Implemented education by parents builds children's readiness to adapt and learn new things, also have an impact on overall children's intelligence and emotional development. This study aims to obtain information about the types of parenting learning needs that are suitable for parents who have children’s, especially those who live along the Sukamakmur District, Bogor Regency, West Java. Researchers used a qualitative descriptive approach. The subjects of this study are elderly people with a vulnerable age of 17 to 60 years, the number of samples to be studied is 397 people. The results showed that the learning needs of parenting people are ways to overcome the problem of eating in infants, foster independence in children, overcome conflicts between children, teach worship, handle children entering  puberty, how to limit children from gadgets / cellphones, controlling while parents far away (LDR), the most pleasing thing about caregiving is when the child is active, the thing that most parents worry about is health problems and fall into negative society.